Congenital Pulmonary Alveolar Proteinosis - Saber Hammami; Khaled Harrathi; Khaled Lajmi; Samir Hadded; Chebil Ben Meriem; Mohamed Néji Guédiche (Case Reports in Pediatrics)
Pulmonary alveolar proteinosis (PAP) is a rare syndrome characterized by pulmonary surfactant accumulation within the alveolar spaces. It occurs with a reported prevalence of 0.1 per 100,000 individuals. Two clinically different pediatric types have been defined as congenital PAP which is fatal and a late-onset PAP which is similar to the adult form and less severe. The clinical course of PAP is variable, ranging from spontaneous remission to respiratory failure. Whole-lung lavage is the current standard treatment for PAP patients. We report a new congenital case of PAP.